If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 = 0.5 * 2(6 + x) Multiply 0.5 * 2 10 = 1(6 + x) 10 = (6 * 1 + x * 1) 10 = (6 + 1x) Solving 10 = 6 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 10 + -1x = 6 + 1x + -1x Combine like terms: 1x + -1x = 0 10 + -1x = 6 + 0 10 + -1x = 6 Add '-10' to each side of the equation. 10 + -10 + -1x = 6 + -10 Combine like terms: 10 + -10 = 0 0 + -1x = 6 + -10 -1x = 6 + -10 Combine like terms: 6 + -10 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4
| 6x+3=9(x-4) | | 8x^2y+12xy^2= | | 6x+3=9x | | 1m-5=3m | | 7/9=y+5 | | 5(c-1)+69=-3c | | 12(x+7)=4(x-1) | | 80+-2y=70 | | 4b^2-9b-34=0 | | U+4/5=-1/6 | | 0=6n-n^2 | | 30x-4=4(2x-0.3) | | -11x^2+1430x-4400=0 | | Y-7/8=-1/2 | | (x-10)+2y=70 | | 6(x-4)=-2x+24 | | 24(1/8y+37.5)+19y=1340 | | 6x+14=-7+x | | 4(x-1)=-3x+31 | | 9(3n-3)=(8n+4)+7 | | 14+6x=7-x | | 6g+7=-29 | | (2x+7)/8-2=x+(x-1)/2 | | 0=7(6-3x) | | 5.5(x-1)=0.5x+24.5 | | (t^2+7t-3)+(t^2+2t)= | | -0.3(2x-5)=0.7(6-x) | | x^3-9x^2-3x-27=0 | | 0.6x-3.6=0.6 | | (x/3)+x=(-10/9) | | x-1/6=-4/5 | | 0=-48+20p-2p^2 |